Huumori ja meänkielisten tilallinen identiteetti - Ridanpää, Juha (Suomen Kansantietouden Tutkijain Seura, 2017)
This article discusses how the spatial identity of linguistic minorities is constructed and shaped through humour. The research focuses on the Meänkieli speaking minorities living in the Torne Valley in Sweden. The research question is approached with the concept of narrative identity, which refers to how individuals and groups build the stories of their self-concept within the context of wider social and cultural discourses. Research is based on eight group discussions, conducted with various cultural workers in the Torne Valley between September 2015 and February 2016, wherein humour was approached simultaneously as a topic of discussion and a mode of narrating. The group discussions disclosed how Meänkieli speaking minorities conceive having a special, unique, and exceptional sense of humour, which is characterized by certain forms of roughness and coarseness as well as a way of experiencing otherness allied with self-irony. In addition, the question whether Meänkieli is a humorous language as such, and by that constitutes a special characteristic of their narrative identity, was one of the key topics during discussions. The research also pointed out how self-irony works as a significant tool for dealing and coping with the minority identity. Tässä artikkelissa tarkastellaan, kuinka kielellisten vähemmistöjen tilallinen identiteetti rakentuu ja muotoutuu huumorin kautta. Tutkimuskohteena on Ruotsin puoleisessa Tornionlaaksossa meänkieltä puhuvat kielelliset vähemmistöt. Tutkimuskysymystä lähestytään narratiivisen identiteetin käsitteen kautta, jolla viitataan siihen, kuinka yksilöt ja ryhmät rakentavat kertomuksen itsestään suhteessa laajempiin yhteiskunnallisiin ja kulttuurisiin diskursseihin. Tutkimus perustuu kahdeksaan syyskuun 2015 ja helmikuun 2016 välillä eri kulttuuritoimijoiden kanssa käytyyn ryhmäkeskusteluun, joissa huumoria lähestyttiin sekä keskustelun temaattisena aiheena että kerronnan muotona. Keskusteluissa kävi ilmi, että meänkieliset kokevat omaavansa erityisen, omanlaatuisen ja poikkeavan huumorintajun, jota luonnehtii mm. härskiys ja rankkuus sekä toiseuden kokemiseen yhdistyvä itseironisuus. Samoin yhdeksi keskeiseksi keskustelun aiheeksi nousi kysymys siitä, onko meänkieli hauska kieli jo itsessään ja tällä tavoin meänkielisten narratiivista identiteettiä luonnehtiva ominaispiirre. Lisäksi tutkimuksessa tuli esille, kuinka itseironia toimii merkittävänä työkaluna vähemmistöidentiteettiä käsiteltäessä.